Uczniowie z niepełnosprawnością w szkołach ogólnodostępnych: nauczanie języków obcych - Karpińska-Szaj, Katarzyna (Neofilolog, 2011)
At present the main purpose of school integration is the pursuit of dialogue and ways of ensuring integration which concerns both disabled learners and the ones who do not exhibit special educational needs. In this paper, the is-sue will be incorporated into the framework of teaching foreign languages to disabled pupils attending public schools. The present author will depict L2 teaching goals in relation to education shared by pupils with and without specific learning difficulties as well as to problems with implementing the idea of integration in foreign language classroom. These questions will be discussed with reference to the opinions of gleaned from public school teachers with experience in working with disabled learners.